Inactivation of Escherichia coli Using Nanosecond Electric Fields and Nisin Nanoparticles: A Kinetics Study - Novickij, Vitalij; Zinkevičienė, Auksė; Stanevičienė, Ramunė; Gruškienė, Rūta; Servienė, Elena; Vepštaitė-Monstavičė, Iglė; Krivorotova, Tatjana; Lastauskienė, Eglė; Sereikaitė, Jolanta; Girkontaitė, Irutė; Novickij, Jurij (Frontiers in Microbiology, 2018)
Nisin is a recognized bacteriocin widely used in food processing, however, being ineffective against gram-negative bacteria and in complex food systems. As a result, the research of methods that have cell wall–permeabilizing activity is required. In this study, electroporation to trigger sensitization of gram-negative bacteria to nisin-loaded pectin nanoparticles was used. As a model microorganism, bioluminescent strain of E. coli was introduced. Inactivation kinetics using nanosecond pulsed electric fields (PEFs) and nisin nanoparticles have been studied in a broad range (100–900 ns, 10–30 kV/cm) of pulse parameters. As a reference, the microsecond range protocols (100 μs × 8) have been applied. It was determined that the 20–30 kV/cm electric field with pulse duration ranging from 500 to 900 ns was sufficient to cause significant permeabilization of E. coli to trigger a synergistic response with the nisin treatment. The kinetics of the inactivation was studied with a time resolution of 2.5 min, which provided experimental evidence that the efficacy of nisin-based treatment can be effectively controlled in time using PEF. The results and the proposed methodology for rapid detection of bacteria inactivation rate based on bioluminescence may be useful in the development and optimization of protocols for PEF-based treatments.